Circulating osteocalcin is increased in early-stage diabetes - Aoki, Atsushi; Muneyuki, Takatoshi; Yoshida, Masashi; Munakata, Hiromi; Ishikawa, San-e; Sugawara, Hitoshi; Kawakami, Masanobu; Kakei, Masafumi (Diabetes Research and Clinical Practice, 2011)
We aimed to examine whether circulating levels of osteocalcin, bone formation marker secreted from osteoblast, are changed in glucose-intolerant subjects without taking glucose lowering agent, because bone metabolism is reportedly related to glucose metabolism in animal and human studies. According to 75g oral glucose tolerance test (75g-OGTT), all subjects (47.6±10.2 years of age; 45 men and 10 women) were divided into three categories: normal glucose tolerance (NGT, n=39), prediabetes (PDM, n=11) that included impaired fasting glucose (IFG) and impaired glucose tolerance (IGT), and diabetes (T2DM, n=5). Serum osteocalcin levels were increased in T2DM as compared to NGT. In all the participants, simple regression analysis model revealed positive correlation of osteocalcin with plasma glucose at 120min, G(120), on 75g-OGTT, negative with both creatinine and Ln(CRP), but not significantly with fasting plasma glucose. Osteocalcin and leptin were independent variables for G(120) (P=0.026 and 0.035, respectively). In multinomial logistic analysis leptin (PDM vs. NGT: P=0.02 Odds ratio (OR) of 1.05, 95% confidence intervals, 1.007–1.084) and osteocalcin (T2DM vs. NGT: P=0.038, OR 10.8, 1.13–102.4) were independently associated. We conclude that circulating osteocalcin and leptin are related to glucose intolerant state.